A idealização do herói em As Minas de Prata, de José de Alencar, sob o enfoque da gramática sistêmico-funcional - Barbosa, Edilberto de Oliveira (2015)
The main purpose of this work is the critical linguistic examination of the hero idealization process in the novel As Minas de Prata, written by José de Alencar. The importance of language in a literary work building process is well recognized but, in practice, the language has received relatively little treatment in an area that plays an essential role. As Minas de Prata, work published in mid-nineteenth century, in the context of the political independence of Brazil, as part of a cultural and political project, reveals its author's efforts to build a hero that represents optimal values for Brazilian developing community. The idealization concerns the use of certain culturally contextualized linguistic choices showing some facts while hiding others in order to guide the reader s construction of meaning. It will be linguistically examined in terms of Appraisal, a system that deals with the writer's position in relation to the message and to the caller considering: Affection, Ethical Judgment of People and Assessment Aesthetic of Objects, proposed by Systemic Functional Grammar (SFG). This theory allows the relationship between linguistic microstructure of Alencar s text and the macro-structure of the speech, in which idealization appears, and is supported by the three simultaneous meanings constructed by language: information, interaction, and text construction. The SFG includes the Critical Linguistics for which any aspect of linguistic structure carries ideological significance. The study answers the following questions: (a) how does the idealization of the hero in As Minas de Prata is carried out? (b) What lexicogrammatical choices are made in terms of Ideational and Interpersonal Metafunctions to express this idealization? Results show the idealization by the construction, through lexical and grammatical choices, of a hero that personifies ideal values: love, piety, and nobility of character; and the proposition of these values to the community through the bond established between the community and the hero